The role of institutional logics during participation in urban processes and projects: Insights from a comparative analysis of upgrading fifteen informal settlements in Kenya. (September 2022) - Wainaina, George Kiambuthi; Truffer, Bernhard; Lüthi, Christoph
Abstract: The academic literature largely acknowledges participation as a key condition for the successful upgrading of informal settlements. However, how individual participative actions of different actor groups and reactions of dwellers combine to influence project outcomes of upgrading processes has not been studied. This article posits that different combinations of presence or absence of collaborative interactions between dwellers and other actors will decisively predict the success and failure of projects. Specifically, we argue that interactions between different groups of implementers and dwellers are conditioned by distinctive value systems—institutional logics—, which provide specific challenges to establishing collaborative interactions with dwellers as the actors conduct their roles. We identify sufficient combinations of participative actions that may lead to successful upgrading using qualitative comparative analysis (QCA) on 15 informal settlements in Kenya's secondary towns that were recently upgraded. Our findings indicate that participation has to consider a multiplicity of actors, who are guided by different logics; it has to span over the whole implementation cycle. It also has to deal reflexively with the issue of representation of the community. This extends the understanding of participation to a perspective that emphasizes the capabilities of implementers to enact collaborative relationships by bridging between their own and the community's institutional logic. Highlights: The article highlights the role of rationalities in how different actors participate due to their different worldviews It introduces an approach to comparative studies of urban processes and actors anchored in institutional logics It explains difficulties for actors to interact with dwellers and how this influences informal settlement upgrading processes The article further expounds on the causal link between participation and project outcomes using configurational theorizing